2003
DOI: 10.1016/s0378-1097(03)00590-1
|View full text |Cite
|
Sign up to set email alerts
|

DmAMP1, an antifungal plant defensin from dahlia (Dahlia merckii), interacts with sphingolipids fromSaccharomyces cerevisiae

Abstract: DmAMP1, an antifungal plant defensin from Dahlia merckii, was shown previously to require the presence of sphingolipids for fungicidal action against Saccharomyces cerevisiae. Sphingolipids may stabilize glycosylphosphatidylinositol (GPI)-anchored proteins, which interact with DmAMP1, or they may directly serve as DmAMP1 binding sites. In the present study, we demonstrate that S. cerevisiae disruptants in GPI-anchored proteins showed small or no increased resistance towards DmAMP1 indicating no involvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 29 publications
(37 reference statements)
1
81
0
4
Order By: Relevance
“…It has been shown that sphingolipids and sterols are enriched in specific domains in the plasma membranes, the so-called membrane rafts (31,32). We demonstrated recently that the interaction between the dahlia plant defensin DmAMP1 and inositolphosphoryl-containing sphingolipids from S. cerevisiae is enhanced by 40% in the presence of equimolar concentrations of ergosterol (12), pointing toward a putative involvement of rafts in the DmAMP1 interaction with the fungal plasma membrane. This is in contrast to the interaction between RsAFP2 and fungal GlcCer, which is not altered by different concentrations of ergosterol.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…It has been shown that sphingolipids and sterols are enriched in specific domains in the plasma membranes, the so-called membrane rafts (31,32). We demonstrated recently that the interaction between the dahlia plant defensin DmAMP1 and inositolphosphoryl-containing sphingolipids from S. cerevisiae is enhanced by 40% in the presence of equimolar concentrations of ergosterol (12), pointing toward a putative involvement of rafts in the DmAMP1 interaction with the fungal plasma membrane. This is in contrast to the interaction between RsAFP2 and fungal GlcCer, which is not altered by different concentrations of ergosterol.…”
Section: Discussionmentioning
confidence: 84%
“…In a similar approach, we demonstrated recently the positive effect of ergosterol on the interaction of DmAMP1 with sphingolipids from S. cerevisiae (12). Interaction of 50 nM RsAFP2 with different concentrations of ergosterol (ranging from 0.1 nmol to 5 nmol coated/well) was assessed.…”
Section: Rsafp2 Interacts With Fungal Glccer But Not With Soybean or mentioning
confidence: 97%
See 1 more Smart Citation
“…However, some bacteria, particularly Grampositive species, are also inhibited, although the activity is less pronounced than that against fungi. The growth of several fungal species, including several filamentous fungi and yeast cells, was inhibited when incubated with these peptides [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Despite the broad inhibitory activity that plant defensins exhibit against different micro-organisms, scientists know little about their activity against protozoa.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between DmAMP and the yeast membrane could probably occur directly without the involvement of membrane proteins [9,10] and it probably leads to an insertion of the defensin into the membrane, resulting in an alteration of the membrane property and inhibition of fungal growth [11].…”
Section: Introductionmentioning
confidence: 99%